The Educational Institutions of Prophet Muhammad's Era and Their Relevance to Modern Education - Fihri, Ahmad; Rasyidi, Muhib; Amrillah, Rizki; Nuris, Anwar (The Magister of Islamic Education IAIN Pontianak, 2025)
The importance of educational institutions in producing quality human resources was recognized from the very beginning of prophethood, evidenced by the special attention given by Rasulullah SAW to the development of Islamic education. During the initial phase of spreading Islam in Makkah, Prophet Muhammad SAW strategically utilized various institutions as centers for education and da'wah (preaching). Although these institutions were not yet as formal as modern schools or ancient Greek institutions, they played a crucial role in advancing the Muslim community. These institutions served as centers for the regeneration and development of Islamic civilization, laying the foundation for the advancement of knowledge and social development. Among them were: 1) Darul Arqam, the house used for the first, often secretive, teaching of Islam; 2) The Mosque, which functioned as a place for gathering, learning, and discussing social community issues; 3) Suffah, a space connected to the mosque for boarding students and disciples; and 4) Kuttab, an educational institution specifically for children. The significance of this study is to highlight that the architecture of Islamic education was established early on, demonstrating that a commitment to scholarship is an essential foundation for shaping the identity and civilization of the Ummah.